Evaluability Assessment of Indonesian Marine Conservation Areas for Management Effectiveness Evaluation - Arisetiarso Soemodinoto; Mirza Pedju (Marine Science Department Diponegoro University, 2022)
The management effectiveness evaluation of marine conservation areas (MCAs) in Indonesia is often conducted assuming that they are likely to be evaluated periodically. However, for good and reliable results, it is recommended to perform the evaluability assessment prior to any evaluation to determine whether an MCA can be evaluated or not. This study aims to assess the evaluability of MCAs managed by the Ministry of Marine Affairs and Fisheries (MMAF) by reviewing their management plans and effectiveness evaluation tools. By employing a qualitative approach, this study found that (i) the management plans are not conceived to support an effective management of MCAs in the field or the evaluation of management effectiveness; and (ii) the current guidelines for evaluating MCA management effectiveness do not evaluate the expected achievements of management actions relative to biodiversity conservation goals and objectives. As a result, MCAs under MMAF direct supervision are not evaluable, and hence, the evaluations are pointless from a biodiversity conservation perspective. To address this discrepancy, it is recommended that the management effectiveness evaluation should only be applied to MCAs with an effectiveness-oriented management plan and should employ tools or guidelines that are devised to evaluate the achievement of MCA conservation goals and objectives.